2021
DOI: 10.1021/acs.inorgchem.1c02124
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 9-Carbene-9-Borafluorene Monoanion and Selenium: Synthesis of Boryl-Substituted Selenides and Diselenides

Abstract: Reactions of 9-carbene-9-borafluorene monoanion (1) with elemental selenium and selenium-containing reagents are reported. When compound 1 is reacted with grey selenium in THF, various boryl-substituted selenides and diselenides are produced (2−6), including molecules resulting from migration of the carbene ligand Dipp group (Dipp = 2,6-diisopropylphenyl). However, when a similar reaction between 1 and grey selenium is performed in toluene in the presence of 18-crown-6, boryl-substituted selenide 7 is obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…cobalt, 6 copper, [7][8][9][10] iron, 11,12 and manganese, 13 have attracted tremendous attention due to their economic viability and high abundance. 14 The Earth abundant and biologically important nickel metal in the development of electrocatalysts for water oxidation has also been investigated. These nickel catalysts exhibited promising OER activity at lower overpotentials with good catalytic stability.…”
Section: Introductionmentioning
confidence: 99%
“…cobalt, 6 copper, [7][8][9][10] iron, 11,12 and manganese, 13 have attracted tremendous attention due to their economic viability and high abundance. 14 The Earth abundant and biologically important nickel metal in the development of electrocatalysts for water oxidation has also been investigated. These nickel catalysts exhibited promising OER activity at lower overpotentials with good catalytic stability.…”
Section: Introductionmentioning
confidence: 99%
“…56 Recently, we demonstrated that 1 may serve as a single-electron reducing agent with diselenides to undergo subsequent radical coupling. 39 Single-electron transfer (SET) can occur spontaneously, provided the energies of the donor HOMO and acceptor LUMO are close. Quinones are especially susceptible to SET reactions as the carbonyl π* orbital is easily reduced to generate an electronically stabilized ketyl radical anion.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical modeling identifies that these low-field signals are due to a large paramagnetic contribution at boron as a result of reduced HOMO–LUMO gaps in charge-separated borafluorenes. The ability to easily tune the HOMO of 9-carbene-9-borafluorene monoanions not only allows for the modification of the anion’s electronic structure but may also prove useful as a means to control reactivity. , Moreover, when reacting 3 with 9,10-phenanthrenequione and 1,10-phenanthroline-5,6-dione, novel charge-separated boron spirocycles ( 5 and 6 ) are synthesized via carbene elimination, with computational mechanistic studies suggesting this reactivity proceeds via an electron-transfer mechanism. Compounds 5 and 6 display bright green and orange luminescence under UV light and are air-stable in the solid state.…”
Section: Discussionmentioning
confidence: 99%
“…When 9-carbene-9borafluorene monoanion (142) was treated with selenium grey powder, a mixture of boryl-substituted selenides and diselenides including Dipp group transferred products were obtained. [206] However, when the same reaction was performed in toluene with 18-crown-6, boron substituted monoselenide product (143) was obtained only (Scheme 52).…”
Section: Caac Chemistry Of Group 16 Elementsmentioning
confidence: 99%
“…This monomeric species 205 can be regarded as a heavier ketenimine (R 2 C=C=NÀ R) analog with Si and P atoms in place of C and N atoms, respectively. It is surprising to note that dark red color crystals of a dimer [(cAAC)Si(P-Tip)] 2 (206) were isolated instead of monomer 205 (Scheme 63).…”
Section: Persistent Silylene Radical Anionsmentioning
confidence: 99%